Housing Demand Survey for Egypt - World Bank (World Bank, Washington, DC, 2021)
In March 2018, the World Bank finalized an agreement with Central Agency for Public Mobilization and Statistics (CAPMAS) to conduct a demand survey for housing across Egypt. The survey consisted of a sample of 10,300 households across eight governorates. The inclusive housing finance program supports several aspects of the government’s social housing program, including financial aid to low-income households to help them access housing. This aid comes in the form of a subsidy that either complements the down payment and the repayments in the first years of a mortgage loan or contributes to the payment of the rent in the public or the private sector. The Government of Egypt asked the World Bank to advise on conducting a housing demand assessment to understand the differential demand for rental and ownership housing by different income and employment groups and for different types of houses, locations, and regions. The main objective of the study is to provide detailed information on the demand for affordable ownership housing with a mortgage loan, a down payment, and a subsidy and for formal rental accommodation.